2023
DOI: 10.3390/cells12020309
|View full text |Cite
|
Sign up to set email alerts
|

An Inhibitory Role for Human CD96 Endodomain in T Cell Anti-Tumor Responses

Abstract: Immune checkpoint blockade (ICB) therapy involves the inhibition of immune checkpoint regulators which reverses their limitation of T cell anti-tumor responses and results in long-lasting tumor regression. However, poor clinical response or tumor relapse was observed in some patients receiving such therapy administered via antibodies blocking the cytotoxic T lymphocyte-associated protein 4 (CTLA-4) or the programmed cell death 1 (PD-1) pathway alone or in combination, suggesting the involvement of additional i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…A recent study showed that the deletion of CD96 in human T cells is associated with increased leukemia cell-killing activity in vitro [ 34 ]. T cells with a chimeric receptor displaying the extracellular domain of HER2 and the intracellular domain of CD96 showed decreased killing activity against HER2-positive tumor cells compared to T cells lacking the intracellular CD96 domain in vitro and in vivo [ 34 ]. As the role of CD96 in human cells is not yet fully understood, these data indicate that immune inhibitory signaling dominates CD96 function in human T cells as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study showed that the deletion of CD96 in human T cells is associated with increased leukemia cell-killing activity in vitro [ 34 ]. T cells with a chimeric receptor displaying the extracellular domain of HER2 and the intracellular domain of CD96 showed decreased killing activity against HER2-positive tumor cells compared to T cells lacking the intracellular CD96 domain in vitro and in vivo [ 34 ]. As the role of CD96 in human cells is not yet fully understood, these data indicate that immune inhibitory signaling dominates CD96 function in human T cells as well.…”
Section: Discussionmentioning
confidence: 99%
“…The increased expression of CD96 in OSCCs shown by the current study also motivates the investigation of anti-CD96 therapy in oral cancer. This could reverse NK cell exhaustion [ 20 ] and increase the activation of T cells [ 34 ].…”
Section: Discussionmentioning
confidence: 99%